2015
DOI: 10.1038/nm.3925
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α confers cardioprotection through ectopic expression of keratins K8 and K18

Abstract: The adult myocardium demonstrates a unique system of adaptation upon stress stimuli, in an effort to maintain its overall homeostasis. This compensatory mechanism remains a mystery1. Tumor Necrosis Factor-α (TNF-α) is one of the major stress-induced pro-inflammatory cytokines that is up-regulated in heart failure1,2 and its sustained expression is considered detrimental for the heart1,3–9. Although previous studies have shown that lower levels of TNF-α confer cytoprotection in the myocardium following ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 71 publications
0
74
0
9
Order By: Relevance
“…During skeletal muscle repair, satellite cells are major targets of TNFα signaling that promotes the early proliferative stage of myogenesis [43]. In the case of heart, TNFα has a cardioprotective function in mice [44]. On the other hand, mononuclear phagocytes engage in a bidirectional interaction with MSCs [20].…”
Section: Discussionmentioning
confidence: 99%
“…During skeletal muscle repair, satellite cells are major targets of TNFα signaling that promotes the early proliferative stage of myogenesis [43]. In the case of heart, TNFα has a cardioprotective function in mice [44]. On the other hand, mononuclear phagocytes engage in a bidirectional interaction with MSCs [20].…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that TNF desensitizes macrophages to the deleterious effects of secondary inflammatory challenges (tolerization) 76 . Others have described homeostatic effects of TNF in tissue regeneration, such as neuronal remyelination 83 , cardiac remodelling 84 and cartilage regeneration 85 . In addition, TNF has suppressive effects on adaptive immune processes in models of autoimmunity such as autoimmune encephalitis 12 .…”
Section: Role Of Tnf In Health and Diseasementioning
confidence: 99%
“…This is supported by recent animal data that argue that TNF-α may be cardioprotective through its ability to form stress-induced cytoskeleton filaments that prevent deterioration of cardiac function and potentially removal of damaged mitochondria, through the process of autophagy. 47,48 Thus, the wrong therapeutic threshold may have been applied to TNF-α blockade. Although unlikely to occur, should future trials of TNF-α blockade proceed, they should be focused on modestly lowering TNF-α levels using low-dose pharmacological inhibition.…”
Section: Complicate Case Of Tnf-α In Chronic Hfmentioning
confidence: 99%
“…113 For example, cardiac-specific deletion of the NF-κB subunit, p65, showed reduced cardiac hypertrophy after TAC, reduced pathological remodeling, and preserved contractile function, 114 whereas other reports argue for a protective role for the NF-κB pathway. 47,115 These differential effects, some of which are downstream of TLR signaling, but also many other cell surface receptors, reflect that the role of traditional proinflammatory signaling cascades, such NF-κB, are dependent on the cell type and microenvironment in which they are engaged. This emphasizes the importance of cause and the temporal aspect of disease progression after different initial insults.…”
Section: Angii Infusion and Tac: Acute Hemodynamic Changes And Inflammentioning
confidence: 99%